Aktivitas Promosi Melalui Instagram Dalam Membangun Citra Positif Masyarakat Terhadap Wahana Dan Fasilitas Di Hairos Waterpark Medan - Br Surbakti, Kiki Aulia; Haris, Abdul; Hidayat, Taufik Wal (Innovative: Journal Of Social Science Research, 2025)
This study aims to explore the effectiveness of promotion through Instagram in building a positive public image of the rides and facilities at Hairos Waterpark Medan. The main focus of this study is to analyze visual content strategies, interactions with followers, and their impact on public perception and interest in visiting. The approach method in this research is descriptive qualitative using descriptive analysis techniques, namely describing the events studied. Data obtained from digital observation, in-depth interviews with promotion managers, and analysis of Instagram content by selecting uploads that have a high level of interaction, such as likes, comments, and re-shares. The results showed that attractive visual content, the use of interactive features such as Stories and Reels, and quick responses to comments and direct messages contributed significantly to building a positive image of Hairos Waterpark in the community. In addition, this study also revealed challenges in managing social media interactions, including limited human resources and rapid changes in social media trends. This study concludes that promotion through Instagram can be a very effective tool in creating a positive image and increasing the attractiveness of tourist destinations, but requires strategic management for sustainability.